2017
DOI: 10.1002/adfm.201704956
|View full text |Cite
|
Sign up to set email alerts
|

From Fragility to Flexibility: Construction of Hydrogel Bridges toward a Flexible Multifunctional Free‐Standing CaCO3 Film

Abstract: Free-standing CaCO 3 materials are an important member in biological systems because of their existence in many natural organisms such as nacre, shell, and crustacean cuticle. However, toughness of those artificial mineral films is sacrificed once their inorganic content is up to 90%, thus freestanding characteristics have seldom been achieved for CaCO 3 films, let alone their real applications. Herein a fast and simple method for constructing hydrogel "bridges" for CaCO 3 microparticles is presented, developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Doped ZnO seed‐nanoparticle polymeric membranes were prepared by phase separation, which enabled a pore‐specific in situ growth of small (<5 μm in diameter) ZIF‐8 islands, as shown in Figure 8G,H 98 . Wang et al suggested a simple method for constructing hydrogel “bridges” for freestanding CaCO 3 films, 99 Figure 8J shows CaCO 3 microparticles connected to a silk‐like “adhesive,” acting as a spider web. Hydrogel bridges dragged the rigid CaCO 3 particles together, enhanced the flexibility of multifunctional membranes, and provided abundant freedom space among the inorganic particles.…”
Section: Membrane Preparation Methodsmentioning
confidence: 99%
“…Doped ZnO seed‐nanoparticle polymeric membranes were prepared by phase separation, which enabled a pore‐specific in situ growth of small (<5 μm in diameter) ZIF‐8 islands, as shown in Figure 8G,H 98 . Wang et al suggested a simple method for constructing hydrogel “bridges” for freestanding CaCO 3 films, 99 Figure 8J shows CaCO 3 microparticles connected to a silk‐like “adhesive,” acting as a spider web. Hydrogel bridges dragged the rigid CaCO 3 particles together, enhanced the flexibility of multifunctional membranes, and provided abundant freedom space among the inorganic particles.…”
Section: Membrane Preparation Methodsmentioning
confidence: 99%
“…Using this strategy, free-standing two dimensional (2D) sheets have been produced by infiltrating a thin layer of alginate, crosslinked with Ca 2+ , with a carbonate source such as Na 2 CO 3 to form CaCO 3 particles inside the alginate matrix. [34] Similarly, three dimensional (3D) composites have been produced from carboxyfunctionalized cellulose nanofibrils that are assembled into 3D hydrogels [35] or from poly(2-hydroxyl methacrylate) (PHEMA) hydrogels. [36] These composites are tough: They reach yield stresses of 200 MPa [35] while they can be strained by up to 8%.…”
Section: Nacre-inspired Ceramic Compositesmentioning
confidence: 99%
“…Researchers' inspiration for biomineralization comes from the pearl layer, where they found that biominerals with well-defined layered structure are made up of 95 wt% CaCO 3 and 5 wt% organic compounds. [1][2][3] In the process of biomineralization, the interaction between a series of biological macromolecules (such as proteins, [4,5] chitins, [6] polysaccharides, [7][8][9] and inorganic substances promote the deposition of inorganic crystals in organisms and further form organic-inorganic composite materials, it DOI: 10.1002/crat.202100012 also allows organisms to possess complex properties and polytropic forms. [10] CaCO 3 is a kind of sparingly soluble salt, which is utilized by nature to fabricate exceptionally stable and tough materials.…”
Section: Introductionmentioning
confidence: 99%